Medicinal Plant Images - Bell, Ian (Pharmacognosy Communications)
Grevillea spp: Grevillea (family Proteaceae) is a genus of approximately 360 species, most of which are native to Australia, although some species are also native to Indonesia, Papua New Guinea and the South Pacific region. Indigenous Australians used some Grevillea species as a food plant and as a medicine. The leaves and bark in particular were used to treat skin sores, cuts and as a general antiseptic. [ 1 ] Recent studies have verified the antibacterial properties of one species, Grevillea robusta. [ 2 ] This photograph was taken in Brisbane, Australia by Dr Ian Cock in June 2010.